Analisis Lingkungan Belajar Santri Dalam Menumbuhkan Akhlak di Pondok Pesantren Daarul Muhajirin Kota Bogor - M Sulthan Alfadly Thalabi; Ahmad Mulyadi; Suyudi Arif (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
In the midst of the development of globalization there are many problems from moral deviations that hit most students and affect their learning environment. The purpose of this study was to describe what learning environments were found at the Daarul Muhajirin Islamic Boarding School in Bogor City, the implementation of growing students' morals, what obstacles were found in implementing a learning environment that was in accordance with the morals of students at the Daarul Muhajirin Islamic Boarding School. This research is a qualitative field research conducted by choosing phenomenology as the approach. Data obtained via. From this study, information was obtained that the learning environment of the Daarul Muhajirin Islamic Boarding School in Bogor City had infrastructure, learning resources, learning media, and learning implementation activities. the strategy of implementing a polite learning environment climate, and the various obstacles found as well as problem solving solutions. Three important points in the implementation of a polite learning environment climate are carried out integrally, namely through learning, reverence and habituation of noble character in every santri. These three important points facilitate the creation of a climate of polite learning environment in accordance with the morals of the students at Daarul Muhajirin Islamic Boarding School. Keywords: learning environment, students' morals